2013
DOI: 10.1590/0102-311x00131412
|View full text |Cite
|
Sign up to set email alerts
|

Análise das barreiras à utilização de trombolíticos em casos de acidente vascular cerebral isquêmico em um hospital privado do Rio de Janeiro, Brasil

Abstract: O acidente vascular cerebral isquêmico (AVCi) é uma importante causa de sequela e morte. A correta utilização do trombolítico enfrenta várias barreiras. O objetivo foi discutir as barreiras à terapia trombolítica em pacientes que chegam, com sintomas de AVCi agudo, à emergência de um hospital privado do Rio de Janeiro, Brasil. Coorte retrospectiva de pacientes entre 2009 e 2011. Foram admitidos 257 pacientes com suspeita de AVCi. Dos pacientes com diagnóstico confirmado (156), 11,5% (18) foram trombolisados. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 41 publications
1
3
0
2
Order By: Relevance
“…This study showed that IS mostly affected elderly people, without a partner, black or brown, with a monthly family income of less than three minimum wages, and affected males and females in identical proportions, data that are similar to other Brazilian ( 13 , 14 ) and international ( 6 , 15 ) studies.…”
Section: Discussionsupporting
confidence: 88%
“…This study showed that IS mostly affected elderly people, without a partner, black or brown, with a monthly family income of less than three minimum wages, and affected males and females in identical proportions, data that are similar to other Brazilian ( 13 , 14 ) and international ( 6 , 15 ) studies.…”
Section: Discussionsupporting
confidence: 88%
“…A deficiência de conhecimento sobre os sintomas e necessidade de atendimento precoce no AVC e outras dificuldades como transportes e busca de serviço médico anterior retardam o atendimento adequado ao paciente. (19) As recomendações atuais apontam para a organização de sistemas integrados de atenção ao AVC incluindo o acionamento dos serviços de saúde pré-hospitalares. Isso envolve a necessidade de outros serviços terciários contra referenciarem pacientes em janela terapêutica para centros especializados em AVC em tempo oportuno.…”
Section: Discussionunclassified
“…The number needed to treat in these studies ranged from 3 to 5 ( Figure). Despite several published studies having shown that much of the population cannot identify the symptoms of stroke, resulting in a delay reaching the hospital 4,5,6,7,8 , we aimed to quantify the current knowledge of physicians regarding the 'state-of-the-art' treatment for acute stroke.…”
Section: Introductionmentioning
confidence: 99%